2019
DOI: 10.1007/s11892-019-1245-z
|View full text |Cite
|
Sign up to set email alerts
|

What the HLA-I!—Classical and Non-classical HLA Class I and Their Potential Roles in Type 1 Diabetes

Abstract: Purpose of ReviewHyperexpression of classical HLA class I (HLA-I) molecules in insulin-containing islets has become a widely accepted hallmark of type 1 diabetes pathology. In comparison, relatively little is known about the expression, function and role of non-classical subtypes of HLA-I. This review focuses on the current understanding of the non-classical HLA-I subtypes: HLA-E, HLA-F and HLA-G, within and outside the field of type 1 diabetes, and considers the possible impacts of these molecules on disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 79 publications
0
34
0
Order By: Relevance
“…It has been suggested that during clot formation an amount of sHLA-G is trapped and/or consumed [47] . In addition, there are other causes that can affect sHLA-G level in relation to HLA-G 14-bp Ins/Del polymorphism including therapies and co-morbidities (for instance diabetes and cardiovascular disease), which were not identified in the current study, as it was observed that sHLA-G level may be affected by them [11] , [14] , [17] , [23] , [48] .…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It has been suggested that during clot formation an amount of sHLA-G is trapped and/or consumed [47] . In addition, there are other causes that can affect sHLA-G level in relation to HLA-G 14-bp Ins/Del polymorphism including therapies and co-morbidities (for instance diabetes and cardiovascular disease), which were not identified in the current study, as it was observed that sHLA-G level may be affected by them [11] , [14] , [17] , [23] , [48] .…”
Section: Discussionmentioning
confidence: 68%
“…They are involved in presenting viral epitopes to T cells and inducing activation, differentiation and proliferation of these cells to become effective antiviral cells [10] . Whereas, non-classical HLA-class I molecules appear mostly to have immunosuppressive functions [11] .…”
Section: Introductionmentioning
confidence: 99%
“…The classical molecules show high polymorphism and are characterized by unique patterns of transcription, protein structure, and immunological function. Non-classical MHC-I molecules exert functions in both the innate and adaptive immune system and, compared to classical MHC-I, appear to have mostly inhibitory effects on immune cells via interaction with inhibitory receptors [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protective factors at play in alpha cells may include their lower biosynthetic rate, the narrower dynamic range of their secretory response ( 34 ), their lower susceptibility to ER stress-induced apoptosis ( 35 ), and their higher expression of non-classical, inhibitory MHC-I molecules, i.e. human leukocyte antigen (HLA)-E ( 36 ). Moreover, autophagy seems less important for the maintenance of alpha-cell metabolism ( 37 ) than it is for beta cells ( 38 ), possibly making autophagy-related APP pathways less active.…”
Section: Secreting Insulin: the Achilles’ Heel Of Beta Cells?mentioning
confidence: 99%